Thinnest Point of the Cornea Compared with the Central Corneal Thickness of Myopic Eyes Measured with Pentacam Scheimpflug System: Doi: 10.36351/pjo.v40i3.1749 - Muzammil, Zoomar; Sharif Hashmani; Nauman Hashmani; Javeria Saleem; Aiman Monis (Pakistan Journal of Ophthalmology, 2024)
Purpose: Noncontact instruments like Pentacam Scheimpflug imaging allows assessment of corneal Pachymetry with good repeatability and reproducibility as compared to ultrasound. We aimed to differentiate corneal thinnest point and central corneal thickness on basis of magnitude and location, and its relation to age, sex, laterality, spherical equivalent and astigmatism in myopes. Study Design: Correlational study. Place and Duration of Study: Hashmanis Hospital Karachi from March 2021 to May 2021. Methods: We enrolled 92 eyes (38 males, 54 females) of myopic adult patients from age 19-52 years. Pre-screening of myopes (-0.75DS to -8.00DS) included refraction, slit-lamp biomicroscopy and fundoscopy. Participants with ocular disease, previous ocular surgery, contact lens and history of any eye drops use were excluded from the study. Pentacam was used to determine CCT, thinnest corneal thickness (TCT) and vector location of TCT. Results: Majority (77%) of the eyes had myopic astigmatism whereas 23% had simple myopia. We found statistically significant difference between CCT and TCT. Inferotemporal and inferonasal displacements of TCT were noted. No difference was noted between TCT and its location among the two sexes. We observed that alteration among the CCT and TCT in both age groups was statistically significant. Conclusion: CCT and TCT are separate measurements and both are important since their magnitudes and locations might differ greatly especially with age. Both reading have significance in determining post-operative risk of corneal ectasia, assessment for refractive surgeries and early detection of ectatic conditions like keratoconus.